Modeliranje naključnih termomehanskih napetostno-deformacijskih stanj - Nagode, Marko (Strojniški vestnik, 2006)
The isothermal strain-life approach is the most commonly used approach for determining fatigue damage, particularly in low-cycle fatigue. It is used for low, medium and high temperatures if the temperature remains constant during the test. Computationally, it is extremely fast and generally requires elasticfinite-element analyses only. For this reason it has been adapted for variable temperatures. The local temperature-stress-strain behaviour is modelled with an operator of the Prandtl type. The hysteresis loops are supposed to be stabilized and no creep is considered. The consequences of reversal point filtering are analysed. Finally, the approach is compared to several thermo-mechanical fatigue tests and the Skelton model.
Keywords: utrujanje termomehansko; enačbe konstitutivne; stanja napetostno-deformacijska; modeliranje; natezni preizkus; utrujanje materiala; napetost; deformacije; temperaturna odvisnost